SELF DISCLOSURE ANAK REMAJA BROKEN HOME DALAM BERKOMUNIKASI DENGAN ORANG TUA - Winda Mei Lestari; Eka Sari Setianingsih; Farikha Wahyu Lestari (IKIP Siliwangi, 2026)
This study analyzes self-disclosure as an important aspect of interpersonal communication between broken-hearted children and their parents, which plays a role in helping individuals express their thoughts, feelings, and personal experiences. However, not all clients are able to express themselves optimally, especially when influenced by unsupportive family relationships. Therefore, this study aims to describe clients' self-disclosure based on aspects of self-disclosure. This study uses a qualitative approach with a case study design. Data were obtained from four students of Senior High School X through in-depth interviews. Data analysis was conducted using MAXQDA software based on the five aspects of self-disclosure: amount, valence, accuracy and honesty, intention, and intimacy. The results of this study indicate that the level of self-disclosure among clients varies and is influenced by the quality of interpersonal relationships with parents. Clients who have secure emotional relationships tend to show higher levels of self-disclosure, while those with a background of family conflict show lower levels of self-disclosure. Self-disclosure is mostly characterized by negative emotions, situational honesty, and a tendency to avoid sensitive topics. These findings emphasize the importance of a safe and empathetic communication environment in fostering optimal self-disclosure.